(untitled) (Medico Legal Update, 2021)
Globally, the quantity of land and water resources on earth is relatively fixed, while the quality progressively decreased. One of the problems with clean water quality is the hardness level caused by valence cation ions of two metals such as Ca2 +, Mg2 +, Fe2 + and Mn2 +. The purpose of this study is to determine the effect of pine resin (Pinus merkusii) in reducing hardness (CaCO3) in clean water. This type of research is a quasiexperimental study by testing the treatment of hard water using pine resin media (Pinus merkusii) measuring ± 5 cm with variations in the thickness of the media that is 20 cm, 40 cm, and 60 cm by replicating 3 times. The results of this study found that the reduction in hardness at 20 cm media thickness by 42.14%, at 40 cm thickness by 51.58%, and a thickness of 60 cm 73.78%. And the one way ANOVA test results showed the value of the comparison between hardness after filtration was sig.0.00 ? 0.05 so that there was a significant difference between the thickness of the pine resin (Pinus merkusii) 20 cm, 40 cm, 60 cm. The conclusion from the study of water management through filtration using pine resin media (Pinus merkusii) meets the requirements according to the Health Ministry of Indonesia Regulation Number 32 of 2017. Water treatment with pine resin if used for the community should use a thickness of 60 cm. As for researchers, it can further use other variations such as the thickness of the pine resin used.